If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h = 6lw + 6wh + 5hl Reorder the terms: h = 5hl + 6hw + 6lw Solving h = 5hl + 6hw + 6lw Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5hl' to each side of the equation. h + -5hl = 5hl + 6hw + -5hl + 6lw Reorder the terms: h + -5hl = 5hl + -5hl + 6hw + 6lw Combine like terms: 5hl + -5hl = 0 h + -5hl = 0 + 6hw + 6lw h + -5hl = 6hw + 6lw Add '-6hw' to each side of the equation. h + -5hl + -6hw = 6hw + -6hw + 6lw Combine like terms: 6hw + -6hw = 0 h + -5hl + -6hw = 0 + 6lw h + -5hl + -6hw = 6lw Combine like terms: 6lw + -6lw = 0 h + -5hl + -6hw + -6lw = 0 The solution to this equation could not be determined.
| -6z-6=12z+12 | | 4+i/4-i | | 4*x^2=11+y^2 | | (5x-9)(8x-7)=0 | | (6x+7)(2x-5)=0 | | (6x-3)+x=32 | | c^2+c+2c-63=0 | | Qd=120-2*30 | | Qd=120-2*50 | | 5/4=y+3/7 | | Qd=120-2*10 | | Qd=120-210 | | (2x^2-5x+2)=0 | | x-(-7x)=5+x | | -5m+24-9(m-1)=7m-(6m-3)-8m+9 | | X/4-3.5=9.9 | | X+5/6=-1/3 | | 9-5?=x-? | | 9-??=x-? | | t^2+12t=36findt | | 1/3(x-4)=4x-3(x-1)+5/3 | | 28x-47=47+28 | | 5=4x+27/3 | | 11/1/3 | | t^2+14t-49=0 | | 5+1/3n=6 | | P=a-b-7 | | 4/5/6/7 | | 5-x/8+3-2x/4 | | -5/3x=35 | | -w+9=-18w-18 | | xsquare+2x-143=0 |